1976
DOI: 10.1210/endo-98-1-48
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phenobarbital and Gonadal Steroids on Periovulatory Serum Levels of Luteinizing Hormone and Follicle-Stimulating Hormone in the Hamster

Abstract: The occurrence of ovulation and serum levels of LH and FSH (measured by radioimmunoassay) were determined in periovulatory hamsters injected with an ovulation-blocking dose of phenobarbital (Phen) combined with progesterone (P), estradiol-17beta (E2), or testosterone (T). Proestrous hamsters were treated at 1300 h with Phen plus oil, P, P plus E2, E2, T, or a second injection of Phen at 2000 h. Each treatment group was divided into 3 subgroups, each of which was serially bled 4 times at 6 h intervals beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The (Zarrow, Yochim & McCarthy, 1964 Bast & Greenwald (1974) for the hamster and LH was assayed by an ovine-ovine assay method described previously (Siegel et al, 1976). The gonadotrophin concentrations were expressed in terms of NIAMDD rat FSH-RP-1 (21 NIH-FSH-Sl) and rat LH-RP-2 (003 NIH-LH-S1), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The (Zarrow, Yochim & McCarthy, 1964 Bast & Greenwald (1974) for the hamster and LH was assayed by an ovine-ovine assay method described previously (Siegel et al, 1976). The gonadotrophin concentrations were expressed in terms of NIAMDD rat FSH-RP-1 (21 NIH-FSH-Sl) and rat LH-RP-2 (003 NIH-LH-S1), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The follicles were classified into 10 stages based on histological criteria: Stages \-<\ consist of 1-4 layers of granulosa cells; Stage 5 has 5-6 layers of granulosa cells with early formation of thecal cells at the 6 layered follicle; Stage 6 has 7-8 layers of granulosa cells; Stage 7 shows incipient development of an antral cavity; Stages 8-10 are small, intermediate and large changes during the periovulatory period suggested that fluctuations in blood gonadotrophin con¬ centrations might not only account for the recruitment of the next set of follicles destined to ovulate but also stimulate the growth of small preantral follicles. The present study was designed to test this possibility by using hamsters in which ovulation was blocked by injecting phenobarbitone at the onset of the critical period on the day of pro-oestrus (Siegel, Bast & Greenwald, 1976), which were hypophysectomized and subsequently treated with FSH (Moore & Greenwald, 1974) and those which were unilaterally ovariectomized (Bast & Greenwald, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…(Bast & Greenwald, 1974). Beginning at 22:00 h on Day 4, there is an increase in serum FSH, accompanied by low levels of LH, which is sustained throughout the afternoon of Day 1 (Siegel, Bast & Greenwald, 1976 (Peluso & Steger, 1978) and causes follicular recruitment in the rat (Hoak & Schwartz, 1980) and in the hamster (Greenwald, 1975;Greenwald & Siegel, 1982). Eshkol & Pariente (1984) have shown that FSH significantly stimulates [3H]thymidine incorporation in rat granulosa cells in culture while hCG has no effect.…”
Section: Isolation Offolliclesmentioning
confidence: 99%
“…To conserve animals, blood was collected from unanesthetized animals at 1330 h by cardiac puncture and at 1700 h by decapitation. This methodology has been used to obtain serial reproductive hormone measurements from Syrian hamsters in our laboratory (Stetson et al 1981, Donham et al 1984, 1994, Talamantes et al 1984, Donham & Stetson 1985 as well as other laboratories (Siegel et al 1976, Siegal & Greenwald 1978, Terranova & Greenwald 1979, Jorgenson & Schwartz 1987. We chose to collect blood from unanesthetized animals since commonly used anesthetics perturb hormone levels.…”
Section: Methodsmentioning
confidence: 99%